Gender, violence and regimes of vulnerability in immigration detention: a transnational analysis - Esposito, Francesca (Immigration detention and social harm, 2025)
This chapter examines the gendered, racialised and classed constructions that are deeply embedded in the fabric of everyday life in immigration detention centres in Italy, Portugal and the UK, and the ways they underpin hierarchies of vulnerability and deservingness. Drawing on traditions of Black feminist thought, it uses testimonies from detained women, staff and human rights workers to explore how gendered violence is conceptualised and addressed in these sites. Notwithstanding their difficult experiences, women who are detained attempt to reject their treatment. In foregrounding their accounts and embodied experiences, this chapter seeks to contribute to a feminist abolitionist critique of immigration detention, grounded in a recognition of the ways that immigration detention reproduces violence.